Green Supply Chain Decision Making and Contract Coordinaion: The Influence of Brand Reputation and Consumer Reference Effects on Low-Carbon Levels - Wang, Wei; Cai, Aiting; Dai , Panqian (Transformations In Business & Economics, 2025)
Rapid economic growth leads to severe pollution and excessive resource consumption, which poses challenges to sustainability. To address these issues, green supply chain management was promoted by the government, encouraging firms to enhance their low-carbon reputation and meet the increasing consumer demand for ecofriendly products. This study developed a differential game model for a two-echelon green supply chain that incorporated consumer reference effects on low-carbon levels-a factor that was often overlooked in previous research. By considering retail price, advertising investment, and emission reduction effort as decision variables, the optimal strategies under decentralized and centralized decision making were analyzed. Results show that centralized decision making leads to higher emission reduction, a stronger reputation, and better financial performance, although its efficiency depends on investment intensity. To bridge the gap between decentralized and centralized decision making, we proposed three contract coordination mechanisms: (i) two-way cost-sharing, (ii) revenue-sharing, and (iii) a hybrid contract. Particularly, the hybrid contract best aligns supply chain performance with the centralized optimum, thereby enhancing profitability for manufacturers and retailers. Numerical analysis validated the findings, providing insights for sustainable supply chain management and low-carbon policy formulation.
Keywords: consumer reference effect; low-carbon product reputation; green supply chain management; differential game theory; contract coordination